Application of Traditional Chinese Medicine nursing technology in pain control after hemorrhoid surgery (痔术后中医疼痛护理的应用现状) - FAN Yanan (范亚楠); XU Yunxia (许云霞); LI Jinghuan (李靖嬛) (Association of Integrative Nursing, 2023)
The incidence of pain after hemorrhoid surgery has been increasing recently years, affecting patients' prognosis and quality of life. Traditional Chinese Medicine nursing technology has its advantages in postoperative pain relief. This paper summarized the research status of Traditional Chinese Medicine nursing technology in pain control after hemorrhoid surgery, and provided reference for pain control in patients undergoing hemorrhoid surgery. (痔术后疼痛发生率较高, 严重影响患者预后和生活质量。中医护理技术在缓解术后疼痛方面有其特色和优势。本研究就痔术后中医疼痛护理的应用现状进行总结分析, 旨在为缓解痔术后患者的疼痛提供更多护理支持。)